Annual report 2018: CGIAR Research Program on Policies, Institutions, and Markets - CGIAR Research Program on Policies, Institutions, and Markets (International Food Policy Research Institute, 2019)
In 2018, research conducted under the CGIAR Research Program on Policies, Institutions, and Markets (PIM) informed policies, strategies, and investments of several governments, development organizations, non-governmental organizations, and private companies in many countries in Africa south of the Sahara, Asia, and Latin America. For instance, PIM contributed to shaping climate change mitigation policies in the Philippines; innovations in agricultural advisory services in India, Kenya, Malawi, and Rwanda; biosafety systems in Malawi; national investment plans in China, Malawi, and Rwanda; food policies in Pakistan; seed distribution and marketing in Ethiopia; value chain improvements for women in Honduras; safety net programs in Bangladesh, Egypt, and Mali; and improved rangeland governance in Tanzania. The Women’s Empowerment in Agriculture Index results influenced many strategies and programs.